2020
DOI: 10.1111/acel.13256
|View full text |Cite
|
Sign up to set email alerts
|

Data mining of human plasma proteins generates a multitude of highly predictive aging clocks that reflect different aspects of aging

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 129 publications
2
76
0
Order By: Relevance
“…Unsurprisingly, DNAme-based clocks built in ORCADES were able to estimate age in both Scottish (Generation Scotland) and Estonian Biobanks (EBB), as the Hannum and Horvath epigenetic clocks have been used successfully in numerous populations. We showed for the first time that clocks built from Olink PEA-based proteomics replicate (in EBB and Croatia-Vis), while clocks built using the SOMAlogic 20 proteomics platform have been shown to replicate across populations previously. Our UPLC IgG glycomics clock also replicated in an independent population, mirroring the applicability of published GlycanAge measures 17 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Unsurprisingly, DNAme-based clocks built in ORCADES were able to estimate age in both Scottish (Generation Scotland) and Estonian Biobanks (EBB), as the Hannum and Horvath epigenetic clocks have been used successfully in numerous populations. We showed for the first time that clocks built from Olink PEA-based proteomics replicate (in EBB and Croatia-Vis), while clocks built using the SOMAlogic 20 proteomics platform have been shown to replicate across populations previously. Our UPLC IgG glycomics clock also replicated in an independent population, mirroring the applicability of published GlycanAge measures 17 .…”
Section: Discussionmentioning
confidence: 89%
“…The extremely high correlations with chronAge reported, such as the r = 0.97 of the Mega-omics OCA, highlight an issue that has been discussed in prior work: that if enough biomarkers were included in the model it would be possible to perfectly estimate chronAge and, by definition, fail to detect (distinct) BA. Lehallier et al 20 showed that correlation between OCA and chronAge increases with the number of proteins included in the model. Further, it is possible to explain 100% of the variance in chronAge using DNAme data in large samples 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpressing Pck1 in mice extends life span and enhances exercise capacity (Hakimi et al, 2007). We recently found that many proteins which change their expression level with age in plasma can accurately predict human age and are also direct regulators of life span and/or age-related disease (Lehallier et al, 2020). Thus, this attribute appears to be shared between genes and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al characterized the plasma proteomic signature in healthy aging humans and found that GDF15 had the strongest positive association with age (82). GDF15 was found to be one of the proteins in the SASP repertoire in many other studies, indicating the possibility for GDF15 to modulate and/or predict senescence (41,(83)(84)(85)(86)(87)(88). Over expression of human GDF15 in female mice extended lifespan in a study by Wang et al (89).…”
Section: Role Of Gdf15 In Senescencementioning
confidence: 99%